Adverse effects of non-steroidal anti-inflammatory drugs in patients with viral respiratory infections: rapid systematic review - von Philipsborn, Peter (BMJ Open, 2020)
OBJECTIVES: To assess the effects of non-steroidal anti-inflammatory drugs (NSAIDs) in patients with viral respiratory infections on acute severe adverse outcomes, healthcare utilisation, quality of life and long-term survival. DESIGN: Rapid systematic review. PARTICIPANTS: Humans with viral respiratory infections, exposed to systemic NSAIDs. PRIMARY OUTCOMES: Acute severe adverse outcomes, healthcare utilisation, quality of life and long-term survival. RESULTS: We screened 10 999 titles and abstracts and 738 full texts, including 87 studies. No studies addressed COVID-19, Severe Acute Respiratory Syndrome or Middle East Respiratory Syndrome; none examined inpatient healthcare utilisation, quality of life or long-term survival. Effects of NSAIDs on mortality and cardiovascular events in adults with viral respiratory infections are unclear (three observational studies; very low certainty). Children with empyema and gastrointestinal bleeding may be more likely to have taken NSAIDs than children without these conditions (two observational studies; very low certainty). In patients aged 3 years and older with acute respiratory infections, ibuprofen is associated with a higher rate of reconsultations with general practitioners than paracetamol (one randomised controlled trial (RCT); low certainty). The difference in death from all causes and hospitalisation for renal failure and anaphylaxis between children with fever receiving ibuprofen versus paracetamol is likely to be less than 1 per 10 000 (1 RCT; moderate/high certainty). Twenty-eight studies in adults and 42 studies in children report adverse event counts. Most report that no severe adverse events occurred. Due to methodological limitations of adverse event counts, this evidence should be interpreted with caution. CONCLUSIONS: It is unclear whether the use of NSAIDs increases the risk of severe adverse outcomes in patients with viral respiratory infections. This absence of evidence should not be interpreted as evidence for the absence of such risk. This is a rapid review with a number of limitations. PROSPERO REGISTRATION NUMBER: CRD42020176056.